2016
DOI: 10.1002/ps.4318
|View full text |Cite
|
Sign up to set email alerts
|

Structure, function and management of semi‐natural habitats for conservation biological control: a review of European studies

Abstract: Different semi-natural habitats occur on farmland, and it is the vegetation's traits and structure that subsequently determine their ability to support natural enemies and their associated contribution to conservation biocontrol. New habitats can be created and existing ones improved with agri-environment scheme funding in all EU member states. Understanding the contribution of each habitat type can aid the development of conservation control strategies. Here we review the extent to which the predominant habit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
180
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(190 citation statements)
references
References 171 publications
(238 reference statements)
6
180
1
3
Order By: Relevance
“…Moreover, a reason of the non-significant increase in natural enemies could be that such diversified systems do not necessarily provide stable habitats with nonprey resources needed for numerous natural enemies (Lundgren, 2009). Holland et al (2016) reviewed the ability of a diversity of non-crop habitats in Europe to enhance conservation biological control at the local scale. They reported that linear woody (i.e.…”
Section: At the Local Scalementioning
confidence: 99%
“…Moreover, a reason of the non-significant increase in natural enemies could be that such diversified systems do not necessarily provide stable habitats with nonprey resources needed for numerous natural enemies (Lundgren, 2009). Holland et al (2016) reviewed the ability of a diversity of non-crop habitats in Europe to enhance conservation biological control at the local scale. They reported that linear woody (i.e.…”
Section: At the Local Scalementioning
confidence: 99%
“…The importance of SNH for biodiversity and beneficial organisms, such as natural enemies of crop pests, should depend on the habitat type and its characteristic vegetation traits as well as their proportion and spatial distribution in the surrounding landscape (Holland et al., ). In particular, SNH dominated by herbaceous vegetation are expected to considerably differ in their value for beneficial organisms compared to woody SNH (Holland et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of SNH for biodiversity and beneficial organisms, such as natural enemies of crop pests, should depend on the habitat type and its characteristic vegetation traits as well as their proportion and spatial distribution in the surrounding landscape (Holland et al., ). In particular, SNH dominated by herbaceous vegetation are expected to considerably differ in their value for beneficial organisms compared to woody SNH (Holland et al., ). For example, woody SNH offer more shelter from harsh weather conditions and can therefore be particularly important for overwintering arthropods (Rusch et al., ; Sarthou, Badoz, Vaissière, Chevallier & Rusch, ), while herbaceous SNH, and especially flower strips, often provide diverse floral resources (Haaland, Naisbit, & Bersier, ; Tschumi et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Wildfl ower strips (WFS) are one of several types of habitats used by insects in agricultural landscapes (Holland et al, 2016). There is extensive evidence that, when sown at fi eld margins, WFS support a higher abundance and diversity of insects compared to adjacent crops (reviewed by Haaland et al, 2011).…”
Section: Introductionmentioning
confidence: 99%